Is outcome of differentiated thyroid carcinoma influenced by tumor stage at diagnosis?. Issue 1 (January 2015) - Clement, S.C.; Kremer, L.C.M.; Links, T.P.; Mulder, R.L.; Ronckers, C.M.; van Eck-Smit, B.L.F.; van Rijn, R.R.; van der Pal, H.J.H.; Tissing, W.J.E.; Janssens, G.O.; van den Heuvel-Eibrink, M.M.; Neggers, S.J.C.M.M.; et al.
Highlights We answered the question: "is detection of Differentiated Thyroid Carcinoma (DTC) at an early stage beneficial?". Early detection of DTC is beneficial for children (very-low level evidence). Early detection of DTC clearly improves outcome in adults (moderate to high level evidence). These results are important for the development of DTC surveillance guidelines.